2015
DOI: 10.1177/1535370214565989
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Sonic hedgehog signaling and WW domain containing oxidoreductase WOX1 expression enhances radiosensitivity of human glioblastoma cells

Abstract: WW domain containing oxidoreductase, designated WWOX, FOR or WOX1, is a known pro-apoptotic factor when ectopically expressed in various types of cancer cells, including glioblastoma multiforme (GBM). The activation of sonic hedgehog (Shh) signaling, especially paracrine Shh secretion in response to radiation, is associated with impairing the effective irradiation of cancer cells. Here, we examined the role of Shh signaling and WOX1 overexpression in the radiosensitivity of human GBM cells. Our results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The use of an antibody to neutralize SHH ligands or a GLI1 silencing approach reversed this protective capability. In GBM, Shh signaling was activated upon IR treatment [ 147 ]. Additionally, cyclopamine treatment increased DNA DSB as indicated by the induction of H2AX, a histone family member that becomes phosphorylated upon DNA breaks.…”
Section: Introductionmentioning
confidence: 99%
“…The use of an antibody to neutralize SHH ligands or a GLI1 silencing approach reversed this protective capability. In GBM, Shh signaling was activated upon IR treatment [ 147 ]. Additionally, cyclopamine treatment increased DNA DSB as indicated by the induction of H2AX, a histone family member that becomes phosphorylated upon DNA breaks.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of SMO represents a promising strategy to overcome therapy resistance in HGG; the Smoothened inhibitor cyclopamine has been shown to induce radiosensitization in glioblastoma cells and Erismodegib, another SMO inhibitor, was capable of inhibiting self-renewal and EMT in glioblastoma initiating cells [ 211 , 212 ]. Additionally, chemical inhibition of the hedgehog pathway could sensitize glioma stem cells to temozolomide [ 213 ].…”
Section: External Initiation Of the Epithelial-to-mesenchymal Transitmentioning
confidence: 99%
“…The biological activities of zerumbone include anti-inflammation, 14 antitumor, 15 - 17 antiproliferation, 18 and antiplatelet aggregation. 18 , 19 In a previous study, zerumbone was also found to enhance the radiosensitivity of WOX1-overexpressed U373MG and U87MG cells 22 by downregulating the Gli-1/B-cell lymphoma 2 (Bcl-2) pathway. In addition, it has been reported to act as a radiosensitizer by promoting ROS-mediated DNA damage.…”
Section: Discussionmentioning
confidence: 94%